Protecting Start-Up Workers: Social Security and Decent Employment in the Gig Economy Era - Agusmidah; Holongi Theonia Lampungu Sitorus; Fithriatus Shaliha; Afriansyah Tanjung; Arum Anggraeni Maulida (Universitas Negeri Semarang, 2025)
The growth of start-ups in Indonesia in the GIG economic era brings new challenges related to social security protection for workers. This study aims to examine the legal protection of start-up workers in obtaining social security and decent working conditions, especially in the context of the risk of losing their job. The main problem raised is the lack of optimal regulations that protect startup workers who are generally informal and do not have formal employment relationships. The research method used is a normative legal method with a statute and conceptual approach, using primary, secondary, and tertiary legal materials. The results show that startup workers face high vulnerability to termination of employment (PHK) without adequate social security protection. Although there is a unemployment benefits program through the Job Creation Law, its implementation is not inclusive of non-formal workers. This study concludes the need for regulatory changes to be more inclusive, as well as the need to recognize the status of startup workers in the social protection system. Collaborative efforts between governments, startups, and digital platforms are essential to expand social security coverage, to ensure decent working conditions for all workers in the digital age and GIG economy.